Implementasi Edukasi Interaktif Berbasis Teka-Teki Silang dalam Pencegahan Verbal Bullying di Sekolah Dasar No. 1 Dalung - Helmy Syakh Alam; Eka Grana Aristyana Dewi; I Wayan Ari Putra; I Putu Daniel Januarta Suputra; Anak Agung Ngurah Abimayu Saputra; I Kadek Pranandita Pramudya Putra Anjasmara; I Putu Kartika Satria Wiguna (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Verbal bullying still frequently occurs in elementary school settings, such as physical taunts or name-calling directed at parents, which students often dismiss as jokes. This behavior can negatively impact children's friendships and their sense of comfort while learning at school. This activity was designed to enhance students' knowledge and attitudes regarding verbal bullying and ways to prevent it. The activity was conducted at Dalung State Elementary School 1, involving 21 students through an educational outreach session. The material covered included the concept, forms, impacts, and prevention of bullying. The material was delivered interactively through brief explanations, discussions, and crossword puzzles. A pre-test was administered one week before the session, with 14 students participating, while 15 students took the post-test on the day of the activity. Data analysis of the 14 students who took both the pre-test and post-test showed improvements across all measured aspects, including understanding of bullying (42.9%), understanding of verbal bullying (42.9%), understanding of bullying prevention methods (42.9%), anti-bullying attitudes (21.4%), and commitment to not engage in bullying (28.6%). These results indicate that interactive socialization is effective in improving elementary school students' understanding of and anti-bullying attitudes toward bullying.